Geografia da educação de jovens e adultos desempregados: trabalho abstrato e humanização - Souto, Jackson Vital (2023)
It was due the present research , within its abstract essenc e focusing on the socio spatial and capitalist development, that we structured and set the goals . Thinking on the relation between working demands and Adu lts and Young Adults Education ( EJA), understanding the dialects humanization versus education process , besides the critical analysis of official documents such as Labor and Social Protection Reform BRASIL, 2017) and the Decree Law n º 01, 2001 (BRASIL, 20 21) which institutionalizes the Adults and Young Adults Education to meet market requirements in accor dance with the Common Curricular Pattern (BNCC), the PNA and Distance Education (EaD); as well as the educational attainment of unemployed workers on the EJA context. A critical analysis of the mentioned official documents helped us to develop the third se t of theoretical and methodological questions: the folding mechanisms, considering important aspec ts such as the government reforms, the s tructural unempl oyment, mediated by abstractions related to private interests that involve money, humanization, the re lations of alienation and oppression in social and working demands and the worker’s educational pr ocess. The main reasons of the structural unemployment, under the abstract mediation of money, have deep implications on the educational formation of Adults a nd Y oung A dult learners in the third and forth cycles at Francisca Moura Public School, in the cit y of João Pessoa, PB, reinforcing the idea that percepti on, the conditions and the positions required by the working demands ha ving serious implications in th e complex phenomena of social relationships and the educational process.